A mechanism for proven technology foresight for emerging fast reactor designs and concepts - Anuar N.; Muhamad Pauzi A. (American Institute of Physics Inc., 2023)
The assessment of emerging nuclear fast reactor designs and concepts viability requires a combination of foresight methods. A mechanism that allows for the comparison and quantification of the possibility of being a proven technology in the future, ? for the existing fast reactor designs and concepts is proposed as one of the quantitative foresight method. The methodology starts with the identification at the national or regional level, of the factors that would affect ?. The factors are then categorized into several groups; economic, social and technology elements. Each of the elements is proposed to be mathematically modelled before all of the elemental models can be combined. Once the overall ? model is obtained, the ?min is determined to benchmark the acceptance as a candidate design or concept. The ? values for all the available designs and concepts are then determined and compared with the ?min, resulting in a list of candidate designs that possess the ? value that is larger than the ?min. The proposed methodology can also be applied to purposes other than technological foresight. 2016 AIP Publishing LLC.